UPAYA PENINGKATAN PRODUKTIVITAS SORGUM (Sorghum bicolor L. Moench) MELALUI PUPUK BIOBOOST - CHAIRIL EZWARD; A. HAITAMI; ELFI INDRAWANIS (Universitas Lancang Kuning, 2019)
Research aims to understand the influence of fertilizer bioboost sorghum to productivity. Design used in this research was a random group ( shelf ) non factorials, The treatment of the volume of fertilizer biobost consisting of : A = Without treatment, B = The provision of fertilizer biobost 120 ml / plant, C = The provision of fertilizer biobost 240 ml / plant, D = The provision of fertilizer biobost 360 ml / plant, E = The provision of fertilizer biobost 480 ml / plant. Research various volume fertilizer biobost consisting of 5 treatment 3 times repeated. Thus this research consisting of 15 units of experiment / a plot, every unit experiment consisting of 16 plants and 12 are as sample. The quantity of a crop whole 240 plant. The results of the observation of treatment analyzed each statistically, and when markedly dissimilar will be continued by test further different real honest ( bnj ) 1 percent the first. Based on the research that has been carried out it can be concluded that treatment volume fertilizer Bioobost had have real impact on all parameter observation, where treatment is the best treatment E = The provision of fertilizer biobost 480 ml / plant, with tall plant 188,33 cm, appearing flowers age 68,22 hst, age harvest 103,44 hst, and a weight of dry 113,61 gram/tanaman setara dengan 6,05 ton ha-1.